Sustainable Nutrient Management in Sugarcane Fields - Anna Kusumawati; Syamsu Alam (Universitas Muhammadiyah Palembang, 2021)
The state of sugar in Indonesia which is decreasing in terms of production, the imbalance between production and consumption, can occur due to two things, both on-farm and off-farm. Planting in monoculture for a long period of time will cause reduced soil fertility conditions so that sugarcane productivity decreases. Sustainable nutrient management in sugarcane plantations is an effort made to obtain optimal and profitable productivity, while still trying not to damage the environment so that it can be sustainable and its productivity can be maintained in the long term. Several concepts for sustainability have been put forward by many experts, including the use of site-specific fertilizers, maintaining soil fertility by using sugar processing by-products and the use of humic. It is hoped that some of these application methods can maintain sugarcane plantations to be sustainable.